Pembelajaran Passing Atas Bola Voli Melalui Permainan Sasaran Tembak (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to investigate the application of learning through play passing over a target to improve learning outcomes for students in grade 01 Sidamulya SDN Tegal Year 2014 research was conducted at 01 Sidamulya SDN Tegal, the samples in this study were students of class V are numbered, 38 students. This research is a class act consisting of two cycles where each cycle consists of four stages: planning, action, observation, and reflection The results showed that the application of the method can improve learning outcomes play on volleyball passing the fifth-grade students of SDN Tegal Sidamulya 01 The year 2014.The average value of passing on the learning outcomes of the first cycle (72.84) second cycle (76,52). So that the learning outcome of the first cycle to the second cycle of (3.68). While the number of students who otherwise completed the first cycle of 27 students (71%) and the second cycle of 34 students (89%). The conclusion of this study, that the passing on learning through target shooting game for the fifth-grade students of SDN Tegal Sidamulya 01 2014 can improve student learning outcomes.increase learning outcomes.